Nearby Nature Buffers the Pain Catastrophizing–Pain Intensity Relation Among Urban Residents With Chronic Pain - Wells, Nancy M.; Rollings, Kimberly A.; Ong, Anthony D.; Reid, M. Carrington (Frontiers in Built Environment, 2019)
Pain catastrophizing is among the strongest predictors of pain intensity. This study examined the role of the nearby natural environment in the experience of pain among community-dwelling adults with chronic pain (N=81) living in New York City and explored the notion that attention may underlie nature’s effect. Nearby nature was objectively measured using satellite data. Daily diary data across 14 days was employed to operationalize pain catastrophizing (and subscales: rumination, helplessness, and magnification) and pain intensity. Results indicated that nearby nature buffered the relation between catastrophizing and pain intensity. Moreover, nearby nature moderated the association between pain-related rumination (the most attention-based subscale of pain catastrophizing) and pain intensity, but did not moderate the helplessness-pain intensity or the magnification-pain intensity associations. These results suggest that the mechanism underlying nearby nature’s moderating influence involves attention. Practitioners in search of strategies to reduce pain intensity experienced by community-dwelling chronic pain sufferers might look to a community resource: nearby nature.